2021
DOI: 10.3389/fmicb.2021.681185
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationships Between Microbiota and Metabolites in Soft-Type Ripened Cheese Using an Integrated Omics Approach

Abstract: Cheese ripening is effected by various microorganisms and results in the characteristic flavors of cheese. Owing to the complexity of the microbiota involved, the relationship between microorganisms and components during ripening remains unclear. In this study, metagenomics and metabolomics were integrated to reveal these relationships in three kinds of surface mold-ripened cheeses and two kinds of bacterial smear-ripened cheeses. The microbiota is broadly divided into two groups to correspond with different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 65 publications
(102 reference statements)
1
15
0
Order By: Relevance
“…Moreover, shotgun metagenomic analyses of gene richness, as a possible indicator of microbial community adaptation to different stress conditions, would be useful to reconstruct metabolic pathways connected with specific cheese traits, such as volatile compound production and metabolites that characterize typical cheeses. In this sense, integrated systems biology, combining metabolomics and metagenomics, could improve our knowledge on this subject, as only a few studies to date have combined both techniques [ 88 , 156 , 166 ]. While microbiota-based studies have compared typical and non-typical products, some omics approaches reported differences between typical and industrial products, thus making it difficult to clearly determine the factors that characterize typical food products.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, shotgun metagenomic analyses of gene richness, as a possible indicator of microbial community adaptation to different stress conditions, would be useful to reconstruct metabolic pathways connected with specific cheese traits, such as volatile compound production and metabolites that characterize typical cheeses. In this sense, integrated systems biology, combining metabolomics and metagenomics, could improve our knowledge on this subject, as only a few studies to date have combined both techniques [ 88 , 156 , 166 ]. While microbiota-based studies have compared typical and non-typical products, some omics approaches reported differences between typical and industrial products, thus making it difficult to clearly determine the factors that characterize typical food products.…”
Section: Discussionmentioning
confidence: 99%
“…This parameter influences cheese microorganism composition and microbial activity, mainly due to the contribution of cheese moisture and salt contents [44], which vary within traditional small dairies cheesemaking protocols [43]. These differences are likely to condition the chemical and biochemical reactions upon ripening determined by the microbiota due to selective pressure on microorganisms [45][46][47]. The maturation index, which corresponds to the ratio between soluble nitrogen (WSN) and total nitrogen (TN), established in the Serpa PDO cheese regulation, was set to at least 45% [6].…”
Section: Physicochemical Analysismentioning
confidence: 99%
“…This indicator does not show significant differences concerning the cheese quality, which can be explained by the fact that it is mainly related to primary proteolysis, essentially caused by the coagulating enzymes, native milk proteinases and less related to direct or indirect microbial activity [48]. The microbial activity generally shows a more significant relationship with the quality of the cheese, mainly aroma and flavour, and can, in a way, be evaluated by indicators such as FAAs and compounds resulting from their catabolism (e.g., organic acids, FFAs and volatile compounds) or also by the ratio NPN/TN [8,9,22,[45][46][47][49][50][51]. In our study, we did not find significant differences for this indicator, probably due to the great variability expressed by the high standard deviation for "bad" and "excellent" quality cheeses.…”
Section: Physicochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cheese surface smear also provides a convenient habitat for enterococci, enterobacteria and molds that are usually not expected to belong to the characteristic surface smear microbiota [10][11][12][13]. In particular, Gram-negative bacteria are frequently detected on the cheese surface as well as in the cheese matrix, but in differing abundances [14][15][16][17][18][19][20][21]. Sometimes the presence of Proteobacteria on surface-ripened cheese can result in deterioration of quality, such as purple rind defects caused by indigo-and indirubin-producing strains of Proteus and Psychrobacter [22].…”
Section: Introductionmentioning
confidence: 99%